Importance of impression management of referees: a qualitative study - Mücahit Fişne; Ali Hasaan (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2022)
Referees are major stakeholders in any game as their role is to keep both fairness and justice intact in the game, but despite all their effort and contributions, referees often face criticism. Thus, the purpose of this study is to discuss the prospect of good referee qualities along with impression management for referees to make their impression better in public. The study has adopted a qualitative approach and questioned 19 referees from five different sports (i.e., football, cricket, basketball, volleyball, and handball) and four different countries (i.e., Serbia, Turkey, Pakistan, and Italy regarding their perception of the importance of impression management and if a better image among the public can help them and their decision-making. The study identified three themes: the qualities of a good referee, impression management for referees, and strategies that can help referees to manage their impression better. Strategies were further identified, including pre-match preparation, branding, public apologies, communication skills, and a clear mind.